2021
DOI: 10.1016/j.ynstr.2021.100321
|View full text |Cite
|
Sign up to set email alerts
|

The functional connectome in posttraumatic stress disorder

Abstract: Background Previous fMRI studies of posttraumatic stress disorder (PTSD) have investigated region-specific alterations in intrinsic connectivity but connectome-wide changes in connectivity are yet to be characterized. Understanding the neurobiology of this is important to develop novel treatment interventions for PTSD. This study aims to identify connectome-wide disruptions in PTSD to provide a more comprehensive analysis of nseural networks in this disorder. Methods A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
6
15
1
Order By: Relevance
“…A bias towards greater perceived saliency (reflected as a hyperactive salience network) has been proposed to underlie reduced cognitive capacity (impacting the cognitive control network) and disruptions in internal mentation and sense of self (impacting the default mode brain network) in PTSD (Akiki et al, 2017 ). These findings are consistent with the clinical profile of PTSD insofar as they have been associated with emotional dysregulation, re‐experiencing and numbing or avoidance symptoms in PTSD (Breukelaar et al, 2021 ; Miller et al, 2017 ). On the other hand, chronic hyperconnectivity within hippocampal, thalamic, left frontal and temporal regions has been previously shown to be positively associated with PTSD severity (Dunkley et al, 2014 , 2018 ).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…A bias towards greater perceived saliency (reflected as a hyperactive salience network) has been proposed to underlie reduced cognitive capacity (impacting the cognitive control network) and disruptions in internal mentation and sense of self (impacting the default mode brain network) in PTSD (Akiki et al, 2017 ). These findings are consistent with the clinical profile of PTSD insofar as they have been associated with emotional dysregulation, re‐experiencing and numbing or avoidance symptoms in PTSD (Breukelaar et al, 2021 ; Miller et al, 2017 ). On the other hand, chronic hyperconnectivity within hippocampal, thalamic, left frontal and temporal regions has been previously shown to be positively associated with PTSD severity (Dunkley et al, 2014 , 2018 ).…”
Section: Introductionsupporting
confidence: 81%
“…Altered whole‐brain connectivity has also been reported in PTSD. Studies have found that PTSD participants displayed hypoconnectivity among higher cortical areas and emotion regulation areas such as lateral frontal, supplementary motor area, salience network, DMN, executive control networks and between the parahippocampal and visual cortex areas (Bao et al, 2021 ; Breukelaar et al, 2021 ; Misaki et al, 2018 ; Ross & Cisler, 2020 ). A bias towards greater perceived saliency (reflected as a hyperactive salience network) has been proposed to underlie reduced cognitive capacity (impacting the cognitive control network) and disruptions in internal mentation and sense of self (impacting the default mode brain network) in PTSD (Akiki et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, changes in brain connectivity involving frontoparietal executive control circuits have recently been reported in PTSD and have been linked to behavioural treatment responsivity, highlighting the importance of prefrontal cortex and its connectivity in PTSD (Korgaonkar, et al, 2020). Differences in the functional connectome have been found for PTSD compared to controls (Breukelaar, Bryant, & Korgaonkar, 2021), including reduced connectivity between regions part of the default mode and executive control network, whereas increased connectivity was found between regions involved in emotional and arousal response such as subcortical and limbic areas.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The anterior insula is known to be a major hub in the SN, involved in network switching and predisposing attention to salient interoceptive sensations and exteroceptive stimuli [26]. There have been mixed findings in the literature concerning hippocampal-SN connectivity in PTSD, where some found hyperconnectivity [35, 120], others found hypoconnectivity [121], and yet others found no connectivity differences in those with PTSD, compared to controls[62]. Our analyses, incorporating separate aHipp and pHipp seeded functional connectivity, offer a resolution to these discrepant findings, as we showed increased aHipp, but not pHipp functional connectivity with the anterior insula, consistent with findings of salience detection by the anterior insula [122, 123], which becomes abnormal in PTSD [124].…”
Section: Discussionmentioning
confidence: 99%